![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a/
\(2^{225}=\left(2^3\right)^{75}=8^{75}\)
\(3^{150}=\left(3^2\right)^{75}=9^{75}\)
\(8< 9\Rightarrow8^{75}< 9^{75}\Rightarrow2^{225}< 3^{150}\)
b/
\(12^8.9^{12}=\left(2^2\right)^8.3^8.\left(3^2\right)^{12}=2^{16}.3^{32}\)
\(18^{16}=2^{16}.\left(3^2\right)^{16}=2^{16}.3^{32}\)
\(\Rightarrow12^8.9^{12}=18^{16}\)
c/
\(45^{10}.5^{30}=\left(3^2\right)^{10}.5^{10}.5^{30}=3^{20}.5^{40}\)
\(75^{20}=3^{20}.\left(5^2\right)^{20}=3^{20}.5^{40}\)
\(\Rightarrow45^{10}.5^{30}=75^{20}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
912 = (32)12 = 324
268 < 278 = (33)8 = 324
=> 268 < 324
=> 912 > 268
912 = (32)12 = 324
268 < 278 = (33)8 = 324
=> 268 < 912
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta có: 26^8 < 27^8= (3^3)^8= 3^24 (1)
9^12= (3^2)^12= 3^24 (2)
Từ (1) và (2) => 26^8< 3^24
Hay 26^8< 9^12
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta có
\(26^8< 27^8=\left(3^3\right)^8=3^{24}\)
\(9^{12}=\left(3^2\right)^{12}=3^{24}\)
\(\Rightarrow26^8< 9^{12}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a,\left(-0,125\right)^4=0.125^4=\left(0.5^3\right)^4=0.5^{12}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
d) 812 và 128
Ta có : 812 = (96)2 = 5314412
128 = (124)2 = 207362
=> 534412 > 207362
=> 812 > 128
a) 36 và 63
Ta có : 36 = (32)3 = 93
63 = 63
=> 93 > 63
=> 36 > 63
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(12^8=\left(12^2\right)^4=144^4\)
\(8^{12}=\left(8^3\right)^4=512^4\)
Vì \(144^4< 512^4\Rightarrow12^8< 8^{12}\)
Vậy \(12^8< 8^{12}\)
b) \(\left(-5\right)^{39}=\left[\left(-5\right)^3\right]^{13}=\left(-125\right)^{13}\)
\(\left(-2\right)^{91}=\left[\left(-2\right)^7\right]^{13}=\left(-128\right)^{13}\)
Vì \(\left(-125\right)^{13}>\left(-128\right)^{13}\Rightarrow\left(-5\right)^{39}>\left(-2\right)^{91}\)
Vậy \(\left(-5\right)^{39}>\left(-2\right)^{91}\)
\(12^8.9^{12}=\left(3\right)^8.\left(2^2\right)^8.\left(3^2\right)^{12}=2^{16}.3^{32}\)
\(17^6< 18^6=2^6.\left(3^2\right)^6=2^6.3^{12}< 2^{16}.3^{32}=12^8.9^{12}\)